Motivations of Multiracial women in monoracial sororities at a predominately white institution. Issue 174 (5th November 2021) - Snider, Jeanette
Abstract: This article explores the motivations, and decision‐making factors implored by twelve Multiracial women in various monoracial sororities at a predominately White institution and provides suggestions for practitioners.